Structural and functional domains of the myb oncogene: requirements for nuclear transport, myeloid transformation, and colony formation. - Ibanez, C E (1988)
The v-myb oncogene of avian myeloblastosis virus causes acute myelomonocytic leukemia in vivo and transforms only myeloid cells in vitro. Its product, p48v-myb, is a nuclear protein of unknown function. To determine structure-function relationships for this protein, we constructed a series of deletion mutants of v-myb, expressed them in retroviral vectors, and studied their biochemical and biological properties. We used these mutants to identify two separate domains of p48v-myb which had distinct roles in its accumulation in the cell nucleus. We showed that the viral sequences which normally encode both termini of p48v-myb were dispensible for transformation. In contrast, both copies of the highly conserved v-myb amino-terminal repeat were required for transformation. We also identified a carboxyl-terminal domain of p48v-myb which was required for the growth of v-myb-transformed myeloblasts in soft agar but not for morphological transformation.